2020
DOI: 10.1155/2020/1421287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reactive Injection Compression Molding by Numerical Simulations and Experiments

Abstract: Injection compression molding is an injection molding process with the addition of a compression stage after the injection. This process is useful for the injection molding of precision parts. A stable and controlled manufacturing process is needed to guarantee reliability of complex products, and usually process optimization is achieved by experimental and time consuming approaches. However, for being competitive a minimal market time is a very important requirement and computer simulations can help to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The common practice of setting up an injection molding simulation revealed that the initial mass temperature is often assumed to equal the set temperature of the plasticizing cylinder of an injection molding machine. Ramorino et al [ 16 ] recently compared results from a real manufacturing process and simulation using an acrylonitrile butadiene rubber (NBR) and they hypothesized that the initial mass temperature had negligible effects on the results of the numerical calculations. Contrary findings were obtained in this work by measuring the actual state of the mass temperature profile with the previously described test stand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common practice of setting up an injection molding simulation revealed that the initial mass temperature is often assumed to equal the set temperature of the plasticizing cylinder of an injection molding machine. Ramorino et al [ 16 ] recently compared results from a real manufacturing process and simulation using an acrylonitrile butadiene rubber (NBR) and they hypothesized that the initial mass temperature had negligible effects on the results of the numerical calculations. Contrary findings were obtained in this work by measuring the actual state of the mass temperature profile with the previously described test stand.…”
Section: Resultsmentioning
confidence: 99%
“…Fasching et al [ 14 , 15 ] showed in subsequent research the importance of correct determination of the mass temperature profile after dosing. Direct measurement of this temperature in the plasticizing cylinder is technically not possible, which is why the initial mass temperature in simulations often equals the set (constant) temperature of the plasticizing cylinder defined at the injection molding machine [ 16 ]. Therefore, Fasching proposed a higher initial set temperature for the rubber compound applied in simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mold is opened and the finished part is ejected and allowed to cool naturally to room temperature (Figure 1D). [1][2][3][4] The ICM process provides a quick and convenient approach for the mass production of plastic components with both simple and complex geometries. However, residual stress is easily accumulated within the molded component during the compression and packing stages, and this often leads to the warpage of the component as it undergoes cooling following ejection from the mold.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mold is opened and the finished part is ejected and allowed to cool naturally to room temperature (Figure 1D). 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mold is opened, and the finished component (e.g., a Fresnel lens) is ejected (Fig. 1d) [1][2][3][4]. Compared to the traditional injection molding process, ICM reduces the injection pressure required to fill the cavity and improves the uniformity of the compression force within the mold.…”
Section: Introductionmentioning
confidence: 99%